2011
DOI: 10.2478/v10285-012-0044-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Vegetation Types on Local Climate

Abstract: In the present days the effects of the global climate change can be observed everywhere. The negative impacts of this phenomenon, especially temperature rising, can be felt significantly in the cities of Central Europe. In these areas the effects of the global temperature rising and the urban heat island intensify each other. However, these phenomena grant the opportunity to find the most suitable vegetation types for moderating the warming up of such urban areas. The aim of this study is to provide support in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…only 2-3°C. Considering furthermore the wide repertoire of shading tools and double facades of the contemporary architecture, which are used for reducing the warming up of these buildings in the summer period, it can be said that simply the shading effect of the trees (without even considering their metabolism) is a very significant urban heat island reducing factor on its own (Olah, 2010b). …”
Section: Tree Stands With Closed Canopy Layersmentioning
confidence: 99%
“…only 2-3°C. Considering furthermore the wide repertoire of shading tools and double facades of the contemporary architecture, which are used for reducing the warming up of these buildings in the summer period, it can be said that simply the shading effect of the trees (without even considering their metabolism) is a very significant urban heat island reducing factor on its own (Olah, 2010b). …”
Section: Tree Stands With Closed Canopy Layersmentioning
confidence: 99%
“…Previous research showed that precipitation can increase 4 5 6 with the growth of forest coverage. Different vegetation types also have distinct impacts on the surrounding climate 7 . For example, a coniferous broad-leaved forest and its analogues have a greater impact than other vegetation types on the change of the average annual precipitation trend 8 .…”
mentioning
confidence: 99%